IMPROVING STUDENTS"™ MATHEMATICAL REPRESENTATION ABILITY THROUGH STUDENT WORKSHEETS: A CONTEXTUAL APPROACH ON THE TOPIC OF RELATION AND FUNCTION FOR EIGHTH GRADE STUDENTS OF JUNIOR HIGH SCHOOL 3 BATU AMPAR - Nursanti, Ria (Jurnal Pendidikan Matematika dan IPA, 2019)
This study aims to describe the increase in the mathematical representation ability by students with the application of contextual approach assisted by Students"™ Worksheet (Lembar Kerja Siswa) on the topic of Relation and Function for the eighth grade students of Junior High School 3 in Batu Ampar (SMP Negeri 3). The method used is descriptive method with classroom action research (Penelitian Tindakan Kelas). The subjects were mathematics teachers and students of class VIII. Data collection techniques used are direct observation techniques with a data collection tool is the observation sheet teachers' ability to implementing the learning and observation sheet student"™s abilities of mathematical representation. This research was conducted in 3 cycles, in which the results showed: (1) Increasing the capability of visual representation of the first cycle to the third cycle was 27.5%, (2) Increasing the ability of symbolic representation of the first cycle to the third cycle of 5%, and (3) Improving the ability of verbal representations from the first cycle to the third cycle of 37.5%.